Atrioventricular dromotropathy: evidence for a distinctive entity in heart failure with prolonged PR interval?. Issue 7 (24th November 2017) - Salden, Floor C W M; Kutyifa, Valentina; Stockburger, Martin; Prinzen, Frits W; Vernooy, Kevin
Abstract: Heart failure (HF) is often accompanied by atrioventricular (AV) conduction disturbance, represented by prolongation of the PR interval on the electrocardiogram. Studies suggest that PR prolongation exists in at least 10% of HF patients, and it seems more prevalent in the presence of prolonged QRS duration. A prolonged PR interval may result in elevated left ventricular (LV) end-diastolic pressure, diastolic mitral regurgitation, and reduced LV pump function. This seems especially the case in patients with heart disease, in whom it is associated with an increased risk for atrial fibrillation, advanced AV heart block, HF, and death. These findings point towards the importance of proper AV coupling in HF patients. A few studies, strongly differing in design, suggest that restoration of AV coupling in patients with PR prolongation by pacing improves cardiac function and clinical outcomes. These observations argue for AV-dromotropathy as a potential target for pacing therapy, but other studies show inconsistent results. Given its potential clinical implications, restoration of AV coupling by pacing warrants further investigation. Additional possible future research goals include assessing different techniques to measure compromised AV coupling, determine the best site(s) of ventricular pacing, and assess a potential influence of diastolic mitral regurgitation in the efficacy of such therapy.